Ecological data on road killed Amphisbaena alba linnaeus, 1758 (Squamata, Amphisbaenidae) in southeast Brazil - De Freitas, Carlos Henrique [UNESP]; De Araujo, Atilarodrigues (My University, 2011)
Vehicles running over vertebrates has been an increasing challenge to the local conservation of some herpetofauna. The Amphisbaenidae are fossorial reptiles which are poorly known ecologically. Biological and natural history data were obtained from three specimens of Amphisbaenia alba that were found dead along 8320 km survey of highways. The rarity of road kill and the importance of the species conservation are discussed.
Keywords: Amphisbaena alba; Amphisbaenia; Amphisbaenidae; Reptilia; Squamata; Vertebrata